2020
DOI: 10.1080/17474124.2020.1782187
|View full text |Cite
|
Sign up to set email alerts
|

Updates in the field of hereditary nonpolyposis colorectal cancer

Abstract: Introduction: Up to one third of colorectal cancers show familial clustering and 5% are hereditary single-gene disorders. Hereditary non-polyposis colorectal cancer comprises DNA mismatch repairdeficient and -proficient subsets, represented by Lynch syndrome (LS) and familial colorectal cancer type X (FCCTX), respectively. Accurate knowledge of molecular etiology and genotype-phenotype correlations are critical for tailored cancer prevention and treatment. Areas covered: The authors highlight advances in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 137 publications
0
16
0
Order By: Relevance
“…Subsequent studies have since identified three RPS20 mutations in familial CRC cases ( 96 , 97 ) and two in Diamond-Blackfan anemia (DBA) patients ( 98 ). Available experience suggests that only a small fraction of FCCTX susceptibility genes have been discovered so far, and that private genes and mutations are common, strengthening the idea of the heterogeneous genetic background of FCCTX ( 94 , 99 ).…”
Section: From Single Genes To the Exome And Genomementioning
confidence: 97%
“…Subsequent studies have since identified three RPS20 mutations in familial CRC cases ( 96 , 97 ) and two in Diamond-Blackfan anemia (DBA) patients ( 98 ). Available experience suggests that only a small fraction of FCCTX susceptibility genes have been discovered so far, and that private genes and mutations are common, strengthening the idea of the heterogeneous genetic background of FCCTX ( 94 , 99 ).…”
Section: From Single Genes To the Exome And Genomementioning
confidence: 97%
“…This gene is a serine–threonine kinase receptor involving the TGF‐β signaling pathway which is a vital regulator of different cellular processes (such as cell proliferation, cell differentiation, and migration). Germline variants in BMPR1A are associated with juvenile polyposis syndrome, MMR‐proficient YOCRC, and unexplained adenomatous polyposis 64 . We identified one patient with a LP variant in BMPR1A and with an MMR‐proficient tumor.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is unclear whether accumulated SBSs promote aging and progressive neurodegenerative diseases as evidenced by the phenotype of MMRdeficient people. MMR-deficiency neither acerates aging nor cause neurodegenerative diseases although the number of newly generated SBSs per division increases nearly 100 times (Peltomäki et al, 2020). Thus, it is an issue of future study to clarify whether a few times increase in the number of SBSs (Table 2) causes neurodegenerative symptom in NER-deficient CS an d XP patients (Lodato et al, 2018).…”
Section: Unsolved Questions and Future Prospectmentioning
confidence: 95%
“…4A, B), are embryonic lethal and die immediately after birth, respectively (Gu et al, 1994;Ludwig et al, 1998).The severe phenotype of BER-deficient animals contrasts with humans deficient in NER and MMR, who develop normally. MMR defects cause carcinogenesis in the colon epithelium in humans due to the accumulation of point mutations and changes in the copy number of STRs during DNA replication (see "Replication errors") (Peltomäki et al, 2020). If excision repair fails to remove base damage before DNA replication, error-prone TLS past damaged template strands converts DNA damage to mutations (see "Spontaneously occurring DSBs in non-dividing cells and during DNA replication" and Fig.…”
Section: Excision Repairmentioning
confidence: 99%